An Variations in Digital Literacy among Primary School Students Based on Regional Context and Teacher Involvement - Siti Muhdiati; Rina Heryani; Nurul Umrotullatifah (Universitas Pendidikan Ganesha, 2025)
The level of digital literacy among primary school students remains relatively low, as reflected in limited access to digital devices and materials, as well as insufficient ability to critically evaluate, filter, and utilize information responsibly. This study aims to analyze the development of digital literacy by teachers and schools and to explore its relationship with students’ digital literacy skills. The research focuses on five main dimensions, information access, digital communication, content creation, digital safety, and technical problem solving. The study employs an ex post facto method with a descriptive comparative quantitative approach. The subjects consist of 336 students and 10 teachers representing various schools. Data were collected through teacher questionnaires and student surveys, and analyzed using descriptive statistics and one way ANOVA to examine differences in digital literacy skills across groups. The results indicate that teacher led digital literacy development varies, while student digital literacy demonstrates significant differences across groups. These findings confirm that successful digital literacy depends not only on school policies or programs but also on the quality of classroom implementation and supportive learning environments. The study highlights the importance of integrating technical, pedagogical, and ethical aspects of digital literacy to enhance 21st-century competencies comprehensively.